Prekmurje v viharju druge svetovne vojne - Dobaja, Dunja (Prispevki za novejšo zgodovino, 2024)
The article focuses on the events in the Prekmurje region during World War II. From 1941 to 1944, this part of the Slovenian territory was almost completely cut off from the rest. The local Partisan movement was largely self-reliant and therefore weak. It received a new impetus in the autumn of 1944, when the first Partisan combat unit, consisting of 36 men, arrived in the Prekmurje region on the orders of the National Liberation Struggle High Command. However, it was soon pushed back across the river Mura. Due to betrayal, the Partisan movement in Prekmurje was once again weakened. At the end of January 1945, the Prekmurska četa company was established in the village of Strehovci but got involved in a fierce battle with the occupying forces and split into several groups. When the Red Army arrived in the Prekmurje region, only a small group of Partisans was in the area.
Keywords: Hungarian occupation; madžarska okupacija; oppression; Prekmurje; Prekmurska četa; represija